THE ROLE OF ENVIRONMENTAL SUSTAINABILITY AND ECONOMIC EFFICIENCY IN THE SUSTAINABLE DEVELOPMENT OF THE ECONOMY (MMIT Proceedings, 2026)
This article examines the transformation of economic sectors and the integration of environmental sustainability and economic efficiency in the context of the development of green technologies. New trends in business greening, green finance, logistics and marketing systems are systematically analyzed, and practical proposals and recommendations are put forward to develop green technologies and increase economic efficiency.
Keywords: green economy; investment attractiveness; environmental sustainability; green finance; green logistics; resource saving